A review of the political stance of Kurdish women: Leyla Zana portrait - Ökzsüzömer, Ecem Hazal (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Uluslararası İlişkiler Anabilim Dalı, 2016)
Bu çalışmanın konusu siyasette etkili bir duruşa sahip olan Kürt kadınlarıdır. Hedef, bu duruşa giden yolda etkisi olan dinamiklerdir. Bu araştırma kadın ve anne imajını merkeze koymaktadır. Konuyu incelerken literatürden ve tarihsel gelişimden yardım alınmıştır. Çalışma, Kürt kadın duruşunu geçmişten günümüze etkili kadın figürleri, siyasi partiler ve onların uygulamaları ile açıklamaya yardımcı olmuştur. Feminizm ve milliyetçilik ile başlayan yol hedeflediği noktaya ulaşmıştır. Kürt kadınının günümüzde diğer kadınlardan farklı olarak geldiği noktayı sergilemiştir. Konu ile çizilen Leyla Zana Kürt kadınını anlamada anahtar niteliğindedir.
Kürt kadınının siyasi duruşu üzerine bir inceleme: Leyla Zana portresi
This study deals with women who have an effective stance in politics. The main objective is to see the dynamics of this stance. This research has centralized the image of women and mother. All through the research, it has been referred to the relevant literature and historical development. The study helped to identify the stance of Kurdish women, influential female figures from the past to the present and political parties with their practices. The road started with Feminism and Nationalism reached its goal, and portrayed the point where the Kurdish women, different from other women, stand. The subject line drawn by the portrait of Leyla Zana is the key factor to help us understand the Kurdish women.
Keywords: Cinsel Politika; Sexual Politics; Etnik Kimlik; Ethnic Identity; Siyasi Kimlik; Political Identity; Siyasi Partiler; Political Parties; Yerel Siyaset; Local Politics